Analisis Interpolasi Inverse Distance Weighted (IDW) Dan Ordinary Kriging (OK) untuk Estimasi Volume Batubara di Area Sebuku Kalimantan Selatan - Sarita, Rahma; Lepong, Piter; Asmaidi, Asmaidi (GEOSAINS KUTAI BASIN, 2024)
ABSTRACT The coal thickness value can be determined through estimation using the inverse distance weighted and ordinary kriging interpolation method. The aim of this research is to determine coal volume estimates using inverse distance weighted (IDW) and ordinary kriging (OK) interpolation in the Sebuku area of ​​South Kalimantan. The estimation process begins with determining the power parameters using the inverse distance weighted method. In this study, a power value of 2 was used and the spherical semivariogram model was used in the ordinary kriging method because it has the smallest Root Mean Square Error (RMSE) value compared to other models. The estimated coal volume using the inverse distance weighted method is 106,436,537.5 m3 and the estimated tonnage is 144,753,691 tons with an average thickness of 5.74 m. Meanwhile, the coal volume estimated using the ordinary kriging method was 101,421,737.5 m3 and the estimated tonnage was 137,933,563 tons with an average thickness of 5.33 m. Keywords: Estimation the coal thickness value, Inverse distance weighted, Ordinary Kriging